Effects of cold water immersion on variables of balance in healthy subjects with open and closed eyes - Simone Sayomi Tano; Karen Barros Parron Fernandes; Auristela Duarte Lima Moser; Deise Aparecida de Almeida Pires-Oliveira; Andre Wilson Oliveira Gil; Rodrigo Franco de Oliveira
AbstractIntroduction Cryotherapy is the use of cold as therapeutic approach. Although often used, its impact on the postural balance is not well-known.Objectives To analyze the effects of cold water immersion in the postural balance on single-leg balance in healthy subjects through the variables of center-of-pressure, velocity anteroposterior and medial-lateral oscillations, comparing conditions open and closed eyes in the moments before, immediately, 20 and 40 minutes after cold water immersion.Material and methods Cross-sectional study with 30 male subjects, cold water immersion at 5 °C during 15 minutes assessed in a force platform, protocol of 3 trials of 30 seconds each with 10 seconds of rest, the average of the 3 trials was used for analysis. The software GraphPad Prisma 5.0 was used for statistical analysis, with the ANOVA test for repeated measures and comparisons with test of Friedman and post-test of Dunn.Results It was observed improvement of the balance by the results of the following variables: in the condition Open Eyes (OE) it was observed significant difference only in the velocity anteroposterior (AP) in the moment before immersion when compared to the 40-minute moment. Significant differences were observed in the condition Closed Eyes (CE) in the following comparisons: in the Center-of-Pressure (COP) only at the immediate moment when compared to the 40-minute moment; in the velocity AP in the moment before when compared to the 40-minute moment, in the immediate moment when compared to the 20-minute and 40-minute moments; and in the medial-lateral velocity (Vel-ML) in two comparisons: in the moment before immersion when compared to the 20-minute and 40-minute moments after cryotherapy. Results show safety in performing activities after cryotherapy.Conclusion Improvement of the postural balance after cold water immersion on the predetermined conditions of this study.